Evaluasi Pengujian Kinerja Menggunakan JMeter untuk Menunjang Stabilitas Aplikasi Layanan Perbankan pada PT Bank Rakyat Indonesia Tbk - Hamidah, Ida; Haromain, Imam; Drehem, Ishom Muhammad (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
The advancement of information technology has had a significant impact on the banking sector, including PT Bank Rakyat Indonesia, which relies on the New Delivery System (NDS) application to support its digital services. NDS is designed to ensure that banking services remain stable, scalable, and fast, even in the face of significant spikes in transaction volumes. As one of BRI's flagship applications, NDS has proven reliable in supporting banking operations. However, performance evaluation is still necessary to ensure the system's readiness to handle growing demands in the digital era. This study uses Performance Testing methods to analyze the performance of NDS using the Apache JMeter tool. Testing is carried out through Load Testing and Stress Testing to measure the application's response under various workloads. Evaluation parameters include response time, throughput, and transaction failure rate. The testing simulates different usage scenarios, from normal to extreme load conditions, to ensure system reliability in various operational situations. The results show that under normal load, NDS has an average response time ranging from 244 ms to 739 ms, throughput of up to 22.26 samples/second, and a transaction failure rate of 0%. However, in high-load scenarios (Stress Testing) with 500 users, the response time increases to 12,691 ms, throughput reaches 36.03 samples/second, and the transaction failure rate is 73.10%. The tests also reveal that CPU usage is close to its maximum capacity (85%), while memory usage remains stable. The analysis shows that NDS requires further optimization in middleware and load distribution to improve application performance and stability. This study provides valuable insights for the development of similar applications in the banking sector to support more stable, efficient, and responsive services.